21.5 dBm‐IIP3 22.5 MHz fourth‐order follow‐the‐leader‐feedback analogue filter. Issue 13 (2nd June 2016) - De Matteis, M.; Pezzotta, A.; Pipino, A.; Baschirotto, A.; D'Amico, S.
Abstract : A 4th‐order single‐loop follow‐the‐leader‐feedback (FLFB) low‐pass continuous‐time filter in CMOS 0.18 µm is hereby presented. The outstanding FLFB noise behaviour is exploited to allocate the power consumption to linearity performance. The low‐pass filter prototype features 22.5 MHz−3 dB frequency, 21.5 dBm‐IIP3 and 76 µVRMS input referred in‐band integrated noise. The overall power consumption is 7 mA from a 1.8 V supply voltage. The signal‐to‐noise ratio for a −40 dB‐total harmonic distortion is 69 dB.